Analysis of fluid flow around a beating artificial cilium - Vilfan, Mojca; Kokot, Gašper; Vilfan, Andrej; Osterman, Natan; Kavčič, Blaž; Poberaj, Igor; Babič, Dušan (Beilstein Journal of Nanotechnology, 2012)
Biological cilia are found on surfaces of some microorganisms and on surfaces of many eukaryotic cells where they interact with the surrounding fluid. The periodic beating of the cilia is asymmetric, resulting in directed swimming of unicellular organisms or in generation of a fluid flow above a ciliated surface in multicellular ones. Following the biological example, externally driven artificial cilia have recently been successfully implemented as micropumps and mixers. However, biomimetic systems are useful not only in microfluidic applications, but can also serve as model systems for the study of fundamental hydrodynamic phenomena in biological samples. To gain insight into the basic principles governing propulsion and fluid pumping on a micron level, we investigated hydrodynamics around one beating artificial cilium. The cilium was composed of superparamagnetic particles and driven along a tilted cone by a varying external magnetic field. Nonmagnetic tracer particles were used for monitoring the fluid flow generated by the cilium. The average flow velocity in the pumping direction was obtained as a function of different parameters, such as the rotation frequency, the asymmetry of the beat pattern, and the cilium length. We also calculated the velocity field around the beating cilium by using the analytical far-field expansion. The measured average flow velocity and the theoretical prediction show an excellent agreement.
Keywords: biomimetics; fluid flow; low Reynolds number hydrodynamics; magneto-optical tweezers; microfluidics